THE EFFECT OF ORGANIZATIONAL CULTURE AND LEADERSHIP UPON JOB SATISFACTION AND JOB PERFORMANCE OF THE EMPLOYEES (The study at PT Promed Farma, Sukabumi, West Java) - Ratno . (The Management Journal of Binaniaga, 2017)
This study aims to examine the effect of the organizational culture and the leadership upon job satisfaction and job performance of the employees. The samples of this study are 125 employees of PT Promed Farma at the manufacturing division applying the proportional random sampling technique. And the hypothesis test has applied the Structural Equation Modelling (SEM) method. The Result of the Analysis has indicated that the organizational culture and the leadership have positively affecting job satisfaction. Organizational culture and job satisfaction have significantly and positively affected job performance of the employees, nevertheless, directly leadership has not significantly affected job performance of the employees. This research has proven that the organizational culture and the leadership have indirectly provided bigger effect upon job performance of the employees when it has been built up thru the highest level of job satisfaction. The variables of the organizational culture, leadership and job satisfaction have determined job performance of the employees which is 75% and the rest of 25% has been determined by other variables that have not been studied yet.Keywords: Organizational Culture, leadership style, job satisfaction and employee performance.